Instant lessons 2 : intermediate - Howard-Williams, Deirdre; Tomalin, Mary.; Watcyn-Jones, Peter; Woods, Edward (England : Penguin English, 2004)
An invaluable resource for busy teachers who need a ready-made lesson or who want to complement their usual teaching material.
Keywords: English language -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; English language